Increased frequency of heart transplantation, shortened waitlist time and preserved post‐transplant survival in adults with congenital heart disease, on the new heart transplant allocation system. Issue 4 (25th February 2021) - Jani, Milena; Cook, Stephen; Huang, Si Hong; Boeve, Theodore; Leacche, Marzia; Manandhar‐Shrestha, Nabin K.; Jovinge, Stefan V.; Loyaga‐Rendon, Renzo Y.
Abstract: Historically, adult congenital patients have longer waitlist time and worse outcomes on the heart transplant waitlist as well as poorer early post‐transplant survival. A new heart transplantation allocation system was implemented in the United States on October 18, 2018. The effect of the new allocation system on adult congenital patients is unknown. Adult congenital patients listed for transplantation between November 1, 2015 and September 30, 2019 registered in the United Network for Organ Sharing were included in the study. October 18, 2018 was used as the limit to distribute listed and transplanted patients into old and new groups. A total of 399 patients were listed for heart transplant only, 284 in the old system and 115 in the new system. Clinical characteristics were similar between both groups. The cumulative incidence of poor outcome on the transplant list was similar in both groups ( P  = .23), but the cumulative incidence of transplant was higher in the new system group ( P  < .009) and was associated with a shorter waitlist time. The one‐year post‐transplant outcome was similar between old and new groups ( P  = .37). The new allocation system has benefited adult congenital patients with increased cumulative frequency of transplantation without worsening short‐term survival after transplantation.